2016
DOI: 10.1016/j.ijscr.2016.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment of retroperitoneal cystic mesothelioma. Two cases reported

Abstract: HighlightsA very rare type of retroperineal malignant cyst tumor is presented on two cases.A very rare type of Mesothelioma tumor is presented on two cases.A minimal invasive type of treatment is proposed instead of the regular open surgery.A small literature review was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Cystic mesothelioma (CM) is a rare lesion that has a predilection for middle-aged women, when it occurs in the abdomen, it is more commonly found in the pelvic space rather than the retroperitoneum [ 18 ]. On MRI, CM typically appears as a hypointense and hyperintense cystic mass on T1- and T2-weighted images, respectively, with minimal to a mild peripheral wall and septal enhancement [ 19 ]. Myxoid liposarcoma is seen in younger populations, with the incidence peaking in the fourth to fifth decades of life.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Cystic mesothelioma (CM) is a rare lesion that has a predilection for middle-aged women, when it occurs in the abdomen, it is more commonly found in the pelvic space rather than the retroperitoneum [ 18 ]. On MRI, CM typically appears as a hypointense and hyperintense cystic mass on T1- and T2-weighted images, respectively, with minimal to a mild peripheral wall and septal enhancement [ 19 ]. Myxoid liposarcoma is seen in younger populations, with the incidence peaking in the fourth to fifth decades of life.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Surgical excision is the treatment of choice of MCPM, either by laparoscopy or by laparotomy. 40,41 However, laparoscopy may underestimate the extent of peritoneal carcinosis. 42 MCPM is considered as a borderline tumor with a risk of neoplasic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Aspiration of its content can reveal the epithelial cell type that may help in determining the histological subtype, however, it is not routinely done as its sensitivity and specificity has been reported low. Additionally, it carries the risk of leakage of the cyst content into the peritoneal space leading a serious pseudomyxoma peritonei or seeding of cells in case of malignancy [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported the use of the SAND balloon catheter, a specially designed catheter which was first described by Ikuma et al in 1998 for laparoscopic ovarian cystectomy [13]. Recurrence rate was reported in 25% in a case series, however, there is no accurate figures in the literature as cases are sporadically reported [1,3,12].…”
Section: Discussionmentioning
confidence: 99%